The moral economy why good incentives are no substitute for good citizens - Bowles, Samuel (New Haven Yale University Press, 2016)
Should the idea of economic man-the amoral and self-interested Homo economicus-determine how we expect people to respond to monetary rewards, punishments, and other incentives? Samuel Bowles answers with a resounding "no." Policies that follow from this paradigm, he shows, may "crowd out" ethical and generous motives and thus backfire. But incentives per se are not really the culprit. Bowles shows that crowding out occurs when the message conveyed by fines and rewards is that self-interest is expected, that the employer thinks the workforce is lazy, or that the citizen cannot otherwise be trusted to contribute to the public good. Using historical and recent case studies as well as behavioral experiments, Bowles shows how well-designed incentives can crowd in the civic motives on which good governance depends.
Parts of this book were given as the Castle Lectures in Yale's Program in Ethics, Politics, and Economics, delivered by Samuel Bowles at Yale University in 2010.
Includes bibliographical references and index.
Keywords: Law and economics; Economics -- Moral and ethical aspects